A History of the Rutgers University Glee Club. - Chapman, David F. (David Francis), 1954- (Rutgers University Press, 2022)
Founded in 1872, the Glee Club is Rutgers University's oldest continuously active student organization, as well as one of the first glee clubs in the United States. For the past 150 years, it has represented the university and presented an image of the Rutgers man on a national and international stage. This volume offers a comprehensive history of the Rutgers Glee Club, from its origins adopting traditions from the German Männerchor and British singing clubs to its current manifestation as a world-recognized ensemble. Along the way, we meet the colorful and charismatic men who have directed the group over the years, from the popular composer and minstrel performer Loren Bragdon to the classically-trained conductor Patrick Gardner. And of course, we learn what the club has meant to the generations of talented and dedicated young men who have sung in it. A History of the Rutgers University Glee Club recounts the origins of the group's most beloved traditions, including the composition of the alma mater's anthem "On the Banks of the Old Raritan" and the development of the annual Christmas in Carol and Song concerts. Meticulously researched, including a complete discography of the club's recordings, this book is a must-have for all the Rutgers Glee Club's many fans and alumni.
Description based upon print version of record.
Keywords: Rutgers University. -- Glee Club -- History.; Rutgers University. -- Glee Club; Glee clubs -- New Jersey -- New Brunswick -- History.; Chanteurs de glees -- New Jersey -- New Brunswick -- Histoire.; MUSIC / General; Glee clubs; New Jersey -- New Brunswick; Glee Club, Rutgers University, performance culture, concerts, singing, songs, college, university, singing culture, choir, music, song, student singing, Männechor Tradition, English Catch Clubs, On the Banks of the Old Raritan, Loren Bragdon, Patrick Gardner, student-run organizations, Howard D. McKinney, Raymond W. Smith, George W. Wilmot, choir gowns, songbooks.; History